Development of the system of psychotherapy of non-psychotic mental disorders and non-compliance in patients with the 2ND type diabetes mellitus - Ткаченко, Ольга Виталіївна (ScienceRise: Medical Science, 2017)
Aim. Development of the system for psychotherapy of non-psychotic mental disorders and non-compliance in patients with the 2nd type diabetes mellitus to improve the treatment of the 2nd type diabetes mellitus in patients having non-psychotic comorbid mental disorders. Materials and methods. 543 patients with the 2nd type diabetes mellitus were examined on the clinical bases of the Therapy, clinical pharmacology and endocrinology department of the State Institution “Zaporizhzhia medical academy of post-graduate education Ministry of health of Ukraine”. The patients were divided in 2 groups depending on the obtained treatment criteria: 270 patients with the 2nd type diabetes mellitus, having treatment with psychotherapy and psycho preventive steps by the developed approaches, formed the studied group. The other 273 patients formed the control group and were treated by the standard clinical protocols. Methods of research: clinical and anamnestic, clinical and psychopathological, psychodiagnostical, and statistical. Results and discussion. In result of research, the system of psychotherapy for the correction of psychopathological and pathopersonal disorders, as well as compliance achievement, in patients having the 2nd type diabetes mellitus was developed. The psychotherapy system consists of three main directions: the first is improvement of compliance to diabetes mellitus therapy and the formation of harmonic lifestyle with diabetes; the second is normalization of patients’ psycho-emotional condition; the third is correction of destructive behavior and personality qualities. The following therapeutic methods were used: psychological education, relaxation, CBT, hypnotic suggestion, body-oriented, rational emotive, and existential. Conclusion. High efficiency of the developed system for neurotic manifestations leveling and improvement of compliance to the 2nd type diabetes mellitus has been proved